Witnessing loss in the everyday: Community buildings in austerity Britain. Issue 1 (January 2019) - Robinson, Katherine; Sheldon, Ruth
This article is concerned with what happens to precarious community buildings in times of austerity. It responds to a landscape of capitalist realism, in which instrumental, economic forms of value are mobilised to justify the closure of ordinary buildings whose survival is not identified as a political priority. The study focuses on two London cases of a library and an elderly day centre under threat of closure, and traces how grammars of austerity rendered these buildings substitutable. Considering how abstract sociological conceptions of value/s can struggle to break into the embedded common sense of austerity, the authors explore how ethnographic practices of collaboration and attentiveness can help amplify alternative expressions of the meanings of these buildings for their communities. Enacting a form of ethnographic witnessing, which learns from Wittgenstein, the authors highlight the creative, vernacular registers and gestures of library users and day centre members, and show how these were anchored in the buildings themselves. In this way, the article supplements noisier, more hyperbolic accounts of the violence of austerity by amplifying quotidian responses, which express how ordinary buildings and the forms of life they sustain, matter.